2004
DOI: 10.1038/nsmb743
|View full text |Cite
|
Sign up to set email alerts
|

A receptor for green tea polyphenol EGCG

Abstract: The major polyphenol in green tea, (-)-epigallocatechin-3-gallate (EGCG), has been shown to prevent carcinogenesis. We have identified a receptor that mediates the anticancer activity of EGCG. Expression of the metastasis-associated 67-kDa laminin receptor confers EGCG responsiveness to cancer cells at physiologically relevant concentrations. Experiments using surface plasmon resonance demonstrate binding of EGCG to the 67-kDa laminin receptor with a nanomolar K (d) value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
510
3
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 626 publications
(546 citation statements)
references
References 8 publications
10
510
3
6
Order By: Relevance
“…Tachibana et al have identified a receptor protein for EGCg. [28] EGCg must interact with the cell membrane before binding to the receptor. Since our results indicate that EGCg interacts with membrane surface and moves freely on the membrane surface, it would be able to bind to its target receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Tachibana et al have identified a receptor protein for EGCg. [28] EGCg must interact with the cell membrane before binding to the receptor. Since our results indicate that EGCg interacts with membrane surface and moves freely on the membrane surface, it would be able to bind to its target receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of telomerase and matrix metalloproteinases has been demonstrated with rather low concentrations of EGCG (IC 50 in the range of 0.5-1 μM). EGCG has also been found to bind to 67-kDa laminin receptor, Bcl-2, vimentin, and glucose-regulated protein 78 with high affinity [50][51][52][53]. However, there are big differences between the effective concentrations determined with pure enzymes and those in cell lines or tissues, possibly due to the nonspecific binding of EGCG to many proteins and the limited amount of EGCG that can enter the cells.…”
Section: Mechanistic Studies On the Activities Of Egcg In Cell Linesmentioning
confidence: 99%
“…the IC 50 observed in a cell-free system was 0.1-0.2 μM, but it was 1-40 μM in tumor cell lines [54]. EGCG was reported to bind to the 67-kDa laminin receptor with a K d of 0.04 μM, to vimentin with a K d of 3.3 nM, and interact with Bcl-2 with a K i of 0.33 μM [50][51][52]. In all these studies, there were experiments demonstrating the biological relevance of the effects in their specific experimental systems, but it required much higher concentrations of EGCG to cause growth inhibition and induce apoptosis.…”
Section: Mechanistic Studies On the Activities Of Egcg In Cell Linesmentioning
confidence: 99%
“…Syncytiotrophoblast formation was monitored in nearly confluent TS cells differentiated for 6 days. In some cases, TS cells were differentiated in the presence of HDAC inhibitor [100 nM trichostatin A (TSA) or 2.5 mM sodium butyrate] (Maltepe et al, 2005) or HAT inhibitor (30 nM curcumin or 5 M EGCG) (Balasubramanyam et al, 2004;Tachibana et al, 2004). For quantification of syncytiotrophoblast formation, cells were incubated with 2.5 m CellMask Deep Red (Invitrogen) for 5 minutes at 37°C and then fixed for 3 minutes in 3.75% formaldehyde at room temperature.…”
Section: Mouse Trophoblast Cell Culture and In Vitro Syncytium Formationmentioning
confidence: 99%